1996
DOI: 10.4039/ent128209-2
|View full text |Cite
|
Sign up to set email alerts
|

VARIABILITY AMONG APHID CLONES OF RHOPALOSIPHUM PADI L. AND SITOBION AVENAE FABR. (HOMOPTERA: APHIDIDAE) IN TRANSMISSION OF THREE PAV ISOLATES OF BARLEY YELLOW DWARF VIRUSES

Abstract: The Canadian Entomologist 128: 199-207 (1996) Attack and emergence of the engraver beetles Ipspini Say and I. latidens LeConte were measured in lodgepole pine (Pinus contorta var. latifolia Engelm.) naturally attacked by the mountain pine beetle, Dendroctonusponderosae Hopk., in 1991. Sample trees were baited with the Ips pheromones ipsdienol and lanierone 1 week and 3 weeks after attack by the mountain pine beetle and again the following spring to observe the effects of the timing of bait placement. The den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
2
13
1
5
Order By: Relevance
“…These results are consistent with those of Rochow & Eastop (1966) who found no significant difference between percentages of PAV (New York isolate) transmission by two clones originating from Illinois and Kansas, under similar experimental conditions (48 h AAP/ 120 h IAP at 21ЊC). Conversely, they conflict with those of Guo et al (1996), who found large differences in percentage of transmission of three PAV isolates (21-91%) among six clones collected in France. There are three possible causes of this discrepancy.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…These results are consistent with those of Rochow & Eastop (1966) who found no significant difference between percentages of PAV (New York isolate) transmission by two clones originating from Illinois and Kansas, under similar experimental conditions (48 h AAP/ 120 h IAP at 21ЊC). Conversely, they conflict with those of Guo et al (1996), who found large differences in percentage of transmission of three PAV isolates (21-91%) among six clones collected in France. There are three possible causes of this discrepancy.…”
Section: Discussioncontrasting
confidence: 83%
“…There are three possible causes of this discrepancy. First, no comparison was made between the clones and virus isolates used here and those used by Guo et al (1996), and PAV-4 could be more easily transmitted overall by R. padi than the isolates tested by these authors. Nevertheless, experiments on another PAV isolate (PAV-13, originating from H. Lapierre, INRA Station de Pathologie Végétale, Versailles France) with a 48 h AAP/120 h IAP, using 11 of the clones from our sample, gave transmission percentages of 90-100% (Sadeghi, unpublished data); this confirms results obtained with PAV-4.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Inter-clonal variation in virus transmission by aphids has been reported for both stylet-borne (Sohi and Swenson 1964;Thottappilly et al, 1972;Jurik et al, 1980;Singh et al, 1983;Lupoli et al, 1992) and circulative viruses (Bjo¨rling and Ossiannilsson, 1958;Robert and Maury 1970;Guo et al, 1996Guo et al, , 1997a. In most cases, variations in the virus-transmitting abilities of different clones were detected.…”
Section: Introductionmentioning
confidence: 94%